Evaluasi Aplikasi Bayar Sekolah pada Yayasan Pendidikan Menggunakan Analisis PIECES di TK Al Hidayah Desa Kepunduhan Tegal - Azizah, Aliyah Nur; Priatna Sari, Yeni; Maulidah, Hikmatul (Publikasi Penelitian Terapan dan Kebijakan, 2024)
Web-based tuition payment management applications are currently widely used by several educational foundations. The use of web-based applications helps foundations in processing SPP records. In 2022, the school payment application was created with the aim of making it easier for the education entity to pay school tuition bills. This research aims to determine the weaknesses and strengths of the school payment application by evaluating the information about, functions, work systems and controls on the school payment application. The analysis in this research is descriptive qualitative. This research uses PIECES analysis indicators, namely: Performances, information, economy, control, efficiency, service. From the results of what researchers conducted through interviews and observations, it can be stated that the existence of a school payment application can make it easier for educational foundations to record cash books. However, there are several indicators that still have weaknesses, including control and information systems that need to be developed